Probing the photointermediates of light-driven sodium ion pump KR2 by DNP-enhanced solid-state NMR - Jakdetchai, Orawan (Sci Adv, 2021)
The functional mechanism of the light-driven sodium pump Krokinobacter eikastus rhodopsin 2 (KR2) raises fundamental questions since the transfer of cations must differ from the better-known principles of rhodopsin-based proton pumps. Addressing these questions must involve a better understanding of its photointermediates. Here, dynamic nuclear polarization–enhanced solid-state nuclear magnetic resonance spectroscopy on cryo-trapped photointermediates shows that the K-state with 13-cis retinal directly interconverts into the subsequent L-state with distinct retinal carbon chemical shift differences and an increased out-of-plane twist around the C14-C15 bond. The retinal converts back into an all-trans conformation in the O-intermediate, which is the key state for sodium transport. However, retinal carbon and Schiff base nitrogen chemical shifts differ from those observed in the KR2 dark state all-trans conformation, indicating a perturbation through the nearby bound sodium ion. Our findings are supplemented by optical and infrared spectroscopy and are discussed in the context of known three-dimensional structures.